1990
DOI: 10.1111/j.1744-7348.1990.tb04226.x
|View full text |Cite
|
Sign up to set email alerts
|

Migratory plant‐parasitic nematodes associated with cereals in Scotland

Abstract: SUMMARYNinety‐eight soil samples were collected from cereal farms on mainland Scotland and examined for migratory plant‐parasitic and predatory nematodes. Soil analysis was also carried out on each sample. Of the 25 parasitic nematode species identified Longidorus elongatus was the most frequently found and while populations were generally low, populations great enough to cause damage were detected. Populations of other plant‐parasites were usually low. Individual species were unlikely to cause economic losses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…have a shorter generation time and smaller body size which can enhance their fast population increase after environmental changes (Yeates & Lee, 1997). Moreover, Boag and Alphey (1988) observed that P. nanus populations increased rapidly a year after nematicide application of 1,3-dichloropropene in a tree nursery field. They concluded that this nematode has an r survival strategy, which means that its numbers increase rapidly in the absence of competition and show seasonal fluctuations.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…have a shorter generation time and smaller body size which can enhance their fast population increase after environmental changes (Yeates & Lee, 1997). Moreover, Boag and Alphey (1988) observed that P. nanus populations increased rapidly a year after nematicide application of 1,3-dichloropropene in a tree nursery field. They concluded that this nematode has an r survival strategy, which means that its numbers increase rapidly in the absence of competition and show seasonal fluctuations.…”
Section: Discussionmentioning
confidence: 96%
“…Currently, growers mainly control nematodes in lettuce by chemical soil disinfestation, which is also applied to reduce several other soilborne pathogens. Boag and Alphey (1988) observed that the population of P. nanus increased drastically after the application of the fumigant 1,3-dichloropropene in a forest nursery field. They concluded that this nematode has an r survival strategy, which means that its numbers increase rapidly in the absence of competition and show seasonal fluctuations.…”
mentioning
confidence: 96%
“…In intensive agricultural systems where the loss of biodiversity leads to low competition levels, drastic increases in the population of Paratylenchus spp. were associated with plant damage (Boag and Alphey 1988;Claerbout et al 2021). However, there is a lack of studies of how they interact with their putative hosts or their population levels in specific crops in systematic sampling schemes.…”
Section: Introductionmentioning
confidence: 99%
“…on potatoes worldwide (Table ), there is still the need for further studies to understand their distribution and impact on potato crops in some countries. In the UK, for example, there are reports of root‐lesion nematodes from infested peas, bean, carrot, barley, and wheat fields (Corbett, ; Boag, , ; Boag and Lopez‐Llorca, ; Boag et al , ; Dale and Neilson, ), but there is no data regarding the affected areas and their impact on potato production.…”
Section: Root‐lesion Nematodes Infecting Potatoes: Biology Infectionmentioning
confidence: 99%